Genetic divergence in Albizia lebbek Benth. provenances in Himachal Pradesh - Thakur, I.K.; Dhuppe, S.G. (Indian Journal of Agroforestry, 2020)
The present investigation was carried out to determine the genetic divergence among morphometric and biomass traits of the progenies of Albizia lebbek selected from fifteen different provenances in the state of Himachal Pradesh. The seedling height contributed maximum (51.10 %) followed by collar diameter (24.50 %) and number of leaves (12.60 %) to the total divergence whereas; the least contribution was shown by dry root weight (0.35%). Following Euclidean cluster analysis all the provenances were grouped into four clusters. Cluster II included (8) maximum number of provenances followed by cluster I (4), whereas cluster IV accommodated minimum (1) provenance. The intra cluster distance was maximum (1.442) in cluster II followed by cluster I (1.439). The generalized inter cluster distance was found highest (7.913) between cluster III and IV and lowest (2.725) between cluster I and cluster II.